Ameliorative effects of phosphorylated peptide from Antarctic krill (Euphausia superba) against H2O2-induced damage in MC3T3-E1 cells - WANG,Shanshan (2022)
Abstract Phosphorylated peptide from Antarctic krill (P-AKP) was prepared by the dry-heating method with sodium pyrophosphate in order to improve its antioxidant activity and osteogenic activity. P-AKP exhibited more competitive DPPH• and OH• scavenging activities compared to the native Antarctic krill peptide (AKP). In hydrogen peroxide (H2O2)-induced oxidative damage of MC3T3-E1 cells, both AKP and P-AKP pretreatment could dose-dependently improve superoxide dismutase (SOD) and catalase (CAT) activities through attenuating the accumulation of reactive oxygen species (ROS) and malondialdehyde (MDA) production. Moreover, AKP and P-AKP prevented oxidative stress-induced down regulation of alkaline phosphatase (ALP) activity and matrix mineralization. Particularly, the promoting effects of P-AKP on the enzymatic antioxidant defense system, differentiation and mineralization was higher than that of AKP. These results suggested that phosphorylation might be a promising approach to improve the antioxidant and osteogenic activity of AKP, and P-AKP could be a beneficial agent for attenuating oxidative stress-related bone loss.